Solid-state compatibility screening of excipients suitable for development of indapamide sustained release solid-dosage formulation - Antovska, Packa; Petruševski, Gjorgji; Makreski, Petre (Informa UK Limited, 2013)
Differential scanning calorimetry and Fourier transform infrared spectroscopy were applied as screening analytical methods to assess the solid-state compatibility of indapamide (4-chloro-N-(2-methyl-2,3-dihydroindol-1-yl)-3-sulfamoyl-benzamide) with several polymers aimed for development of 24 h sustained release solid-dosage formulation. After the initial research phase which was directed towards selection of suitable polymer matrices, based on their solid-state compatibility with the studied pharmaceutical active ingredient, the second phase of evaluation was intended for compatibility selection of other excipients required to complete a sustained release formulation. The preformulation studies have shown that polyvinylpyrrolydone/polyvinyl acetate might be considered incompatible with indapamide, and the implementation of this polymer career should be avoided in the case of the entitled development. The experimental data additionally have revealed that sorbitol is incompatible with indapamide. The obtained results afforded deeper insight in to the solid-state stability of the studied binary systems and pointed out directions for further development of indapamide sustained release solid-dosage formulation.